2020
DOI: 10.20448/journal.512.2020.71.1.6
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of Agriculture and Water Sector and the Reality of Food Security in Arab Countries (2010-2017)

Abstract: The main aim of the paper is to presents the reality of food security in Arab countries (that means literally the Arab peninsula and the North African Arab States); in the light of the efficiency of agriculture and water sector during the period (2010-2017). The descriptive analytical approach was used. Secondary data were collected and used to describe challenges that faced Arab food security during that period. The results found that agricultural production is insufficient to meets the demand for food in Ara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…It has been concluded that silica gel could produce the maximum amount of water as 155 ml/kg/ day. Allagabo and Mustafa (2020) presented food security and water management for Arab countries. In the manuscript, descriptive-analytical approach has been used to describe the challenges faced by Arabian food security during the period 2010-2017.…”
Section: State Of Artmentioning
confidence: 99%
“…It has been concluded that silica gel could produce the maximum amount of water as 155 ml/kg/ day. Allagabo and Mustafa (2020) presented food security and water management for Arab countries. In the manuscript, descriptive-analytical approach has been used to describe the challenges faced by Arabian food security during the period 2010-2017.…”
Section: State Of Artmentioning
confidence: 99%